AKUNTABILITAS DALAM PERSPEKTIF TRADISI KEMATIAN SUA MASYARAKAT BAJAWA - Dawu, Leopold Melkiano Triangga; Moi, Maria Odriana Veronica; Jaja, Aurelius Mikael Lengi (JURNAL DARMA AGUNG, 2023)
The aim of this research is to find the meaning and form of accountability of the SUA Tradition in the Bajawa Society. The concept of accountability can be defined as the accountability or obligation to respond to parties who have the right or authority to request information or accountability regarding the performance and actions of an individual/legal entity/management or collective organization. This type of research is qualitative research. Ethnographic Approach used in this study, data collection was carried out by following observations, in-depth interviews with informants, and documentation. The Sua tradition is a series of death events from the Bajawa people that occur when grieving for a family. The Sua tradition is a series of death events for the Bajawa people, where previously there was grief for a family. The results of the meaning and form of accountability in the SUA death tradition are distinguished in three main dimensions, namely physical, kinship and socio-cultural accountability. The kinship dimension is part of all activities in the SUA tradition, both in the socio-cultural dimension and in the physical dimension.